Fugitive pedagogies: decolonising Black childhoods in the Anthropocene. Issue 3 (3rd May 2020) - Trafí-Prats, Laura
ABSTRACT: The article addresses the concept of Black childhoods through an ontology of fugitivity that operates at the intersection of Black studies and feminist science and technology studies. An ontology of fugitivity thinks of Blackness as a performance of resistance to systems of knowledge that have persistently situated Blackness as placeless and outside sovereign power. The article elaborates this ontology of fugitivity with attention to two concepts, the Black outdoors and a recalibration of the senses. Focusing retrospectively on a series of classroom interactions and art created by one Black girl, Quvenzhané, the article examines how, through processes of artwork, Black childhoods articulate as complex compositions of bodies, images, sound, and non-binary relations of outside-inside. The article concludes with a discussion of how pedagogies that attend to fugitivity can contribute to sensorial and ontological reorientations demanded by the Anthropocene.